Autism in Early Childhood Education Montessori Environments: Parents' and Teachers' Perspectives - Janes, Robyn Dana (Auckland University of Technology, 2015)
There is very little research about children with Autism in Montessori early childhood education in Aotearoa New Zealand. This study examined parents’ and teachers’ perspectives of children with Autism attending Montessori early childhood education environments. This thesis documents literature that explores and critiques Montessori philosophy and the teaching of children on the Autism spectrum. The purpose of this study was to gain insights into the Montessori teaching approach in early childhood education, as a supportive environment for children with Autism in the early years. However, I discovered that the Montessori environment is less than ideal if the teachers do not understand Autism Spectrum Disorder and do not make allowances for the symptoms that present themselves. It was my intention to explore the factors that complemented both Montessori and the support of children with Autism with an approach that is conducive to learning and encourages positive behavioural patterns. The findings revealed three main indicators being identified as important. These were social competence, language and communication, and individual interests and sensory implications. However, not all findings were positive. The parents all agreed that the teachers needed to be flexible and understanding in their approach, and many Montessori teachers are strict in their routine and are not prepared to sway from their teaching method to assist a child with Autism. This study suggests that Montessori early childhood teachers would benefit from professional development in the areas of including children with special needs, particularly Autism Spectrum Disorder, particularly in regards to understanding the unique characteristics of children with Autism and how they can effectively use the Montessori philosophy, equipment and prepared environment to support each child’s learning and development. Suggestions for future professional learning for Montessori teachers include the provision of professional development in including children with “special needs”, particularly Autism Spectrum Disorder for Montessori early childhood teachers. It is not only the Montessori philosophy and the prepared environment that supports the child with Autism, but the teacher’s awareness of the child’s needs and a willingness to be flexible in their approach.
Keywords: Autism; Montessori